FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN WISATAWAN UNTUK MEMBELI PRODUK NON MAKANAN DI OBJEK WISATA RELIGI DESA GIRI KABUPATEN GRESIK - Siti Mundari; Herlina Herlina (Universitas Maarif Hasyim Latif, 2021)
The existence of Sunan Giri's grave in Gresik Regency is a blessing for the surrounding community. The community's economy is lifted and various products are marketed. The tourists in addition to pilgrimages usually also buy souvenirs in the form of food or non-food. The COVID-19 pandemic and Enforcement of Restrictions on Community Activities have caused tourist attractions to be closed, including the religious tourist site of Sunan Giri's cemetary. Business actors were very hit because their products were not absorbed by the market, for that research was conducted to determine the factors that influence tourist decisions in buying products, especially non-food products such as knitting, clothing, hijab, accessories and others at the Sunan Giri tourist attraction. Based on the research results, the factors that influence tourists' decisions to buy non-food products as souvenirs can be explained by the Multiple Linear Regression model Y=0.046 +1.006X1 + 0.019 X2 + 0.539 X3 + 0.246X4. The coefficient of determination is 91.7%, indicating the simultaneous influence of the independent variables of price, product, place of sale and promotion, contributes to the dependent variable of purchasing decisions, while 8.3% is influenced by other factors outside the independent variables studied. Based on the F test the independent variables of price, product, place of sale and promotion simultaneously have a significant effect on the dependent variable of purchasing decisions and the results of the t test show that each independent variable of price, product, place of sale and promotion has a partial effect on the dependent variable on purchasing decisions.AbstraKKeberadaan makam Sunan Giri di Kabupaten Gresik menjadi berkah bagi masyarakat sekitar. Perekonomian masyarakat terangkat dan beraneka produk dipasarkan. Para wisatawan disamping ziarah biasanya juga membeli oleh-oleh baik berupa makanan atau non makanan. Pandemi covid 19 dan aturan PPKM yang ketat menyebabkan tempat-tempat wisata ditutup termasuk tempat wisata religi makam Sunan Giri. Pelaku usaha sangat terpukul karena produknya tidak terserap pasar, untuk itu penelitian dilakukan untuk mengetahui faktor-faktor yang mempengaruhi keputusan wisatawan dalam membeli produk khususnya non makanan seperti rajut, pakaian, hijab, asesoris dan lain-lain di objek wisata Sunan Giri. Berdasarkan hasil penelitian faktor-faktor yang berpengaruh terhadap keputusan wisatawan untuk membeli produk non makanan sebagai oleh-oleh dapat dijelaskan dengan model Regresi Linier Berganda Y=0,046 +1,006X1 + 0,019 X2 + 0,539 X3 + 0,246X4. Nilai kaefisien Determinasi 91,7 %, menunjukan besar pengaruh serentak variabel bebas harga, produk, tempat berjualan dan promosi memberikan sumbangan terhadap variabel terikat keputusan pembelian sedangkan 8,3% dipengaruhi oleh faktor lain diluar variabel bebas yang diteliti. Berdasarkan uji F variabel bebas harga, produk, tempat berjualan dan promosi secara simultan berpengaruh signifikan terhadap variabel terikat keputusan pembelian dan hasil uji t menunjukan masing-masing variabel bebas harga, produk, tempat berjualan dan promosi berpengaruh secara parsial dengan variabel terikat keputusan pembelian.